Dinamika Kehidupan Sosial Ekonomi Masyarakat Nelayan di Desa Kedonganan Kabupaten Badung 1990-2018 - Karlina, Puput; Wirasmini Sidemen, Ida Ayu (Humanis; Vol 24 No 2 (2020), 2020)
The title of this research is the Dynamics of Social Economy of Fishermen in Kedonganan Village 1990-2018.  The formulation of the problems of this study are 1) How is the Life of the Kedonganan People?, 2) What is the role of the Adat Village and the Regional Government?  , 3) What is the dynamics of the socio-economic life of the fishing community in Kedonganan? In this study using the methodology of social history and the theory used is the theory of history and the theory of social change where these two theories can be applied to explain in this research the Historical Explanation theory, namely explaining events in the past, and social change theory that can be seen from the results of research  namely changes that occur in the fishing community Kedonganan.  In this study found the results of fishermen in Kedonganan are not sea fishermen but “land” fishermen